The Modularity of Dyslexia - D.R. Rahul; R.Joseph Ponniah (Elsevier, 2021)
There is a growing interest in understanding dyslexia and the mechanisms involved in reading difficulties. Inquiries into the morphological and physiological changes of the brain have contributed to our increased understanding of reading ability and dyslexia. Similarly, inquiries into brain chemistry and reading provide a neurometabolic framework of dyslexia in terms of poor reading and phonological measures. Also, studies of the genetic etiology of reading yield substantial evidence of genes and SNPs associated with dyslexia. However, little is known about the interface between these distinct areas of knowledge. Therefore, we offer an exhaustive perspective on dyslexia using the idea of modularity by assimilating the findings and implications from the brain morphological, neurophysiological, neurochemical, genetic, and educational insights into dyslexia. We contend that this endeavor will provide a beneficial foundation for aiming at the possibilities of a holistic intervention and informed solutions for reading difficulties.